QUALITY OF LEADERSHIP AND THE IMPORTANCE OF COMMUNICATION IN RELATION TO THE AUTHOR’S PROFESSIONAL ACTIVITY - Cardoso, Gildon (Revista Gênero e Interdisciplinaridade, 2023)
The success of public or private institutions depends a lot on the competence of the leaders. Since they are the head of any hierarchically organized institution, it is important that their actions are focused on results through behaviors that influence the favorable performance of their team and consequent generation of expected results. It is in this context that the communication component must be a strong link between the leader and the subordinates, as well as between the collaborators. In fact, institutional communication must be part of habits and customs in institutions so that there is an environment that favors the development of human capital. Relating the theme to the author’s work environment, it was noted that there are no favorable qualities of leadership in the author’s institution and the importance of communication is not observed, due to the fact that these elements are not part of the institution’s daily life, since the leader is authoritarian and does not agree or even accept the opinion of collaborators. The methodology used for the development of this work was the Bibliographic review.